Any dynamical system is fully accessible through one single actuator and related problems - Kawano, Yu; Kotta, Ülle; Moog, Claude H. (International journal of robust and nonlinear control, 2016)
Summary Whether an autonomous system can be rendered fully accessible through one single actuator is a long‐standing open problem, which got some solutions in special cases when additional constraints are considered. Herein, it is shown that a solution to the general problem is provided as an easy consequence of the straightening theorem. This solution is innovative for linear time‐invariant systems as well and relaxes the well‐known cyclicity condition as it involves nonlinear state transformations. The dual problem of designing one single sensor to render a given system observable obtains a similar almost unconditional solution. Copyright © 2015 John Wiley & Sons, Ltd.